Medieval hagiographic sources and Medical Anthropology. Thaumaturgic saintliness as a cultural device in the defence of health in 12th-14th centuries Orvieto - Petrangeli, Enrico (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
Medieval hagiographic sources and Medical Anthropology. Thaumaturgic saintliness as a cultural device in the defence of health in 12th-14th centuries Orvieto